(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article is devoted to the borrowing words in Anglicism in the Russian language. There has been shown number of words which were added on the speech. On this occasion many scientists developed their own concepts. For instance, Kryisin L.P. in his work «About Russian language these days», contemplates the flow of foreign vocabulary at the intersection of 20th and 21st centuries. Anglicism began being involved in Russian language in the beginning of 19th century. Besides, words can take place from Latin root. Furthermore, in this article have been emphasized neologism words, playing an important part in the function of language. Nevertheless, this «code Language» will be developing and will get an importance in communicative speech.